The effect of light therapy on sleep quality in cancer patients: a systematic review and meta-analysis of randomized controlled trials - Liqing Yao; Zhiyi Zhang; Lawrence T. Lam; Lawrence T. Lam; Lawrence T. Lam (Frontiers in Psychiatry, 2023)
BackgroundSleep problem is one of the major issues of cancer patients and may have detrimental effects on the ongoing treatment and recovery of patients. However, the evidence for the effect of light therapy on sleep problems in this population remained scarce. This study aimed to examine the effect of light therapy on self-reported and physiological measures of sleep quality of cancer patients. It also aimed to quantify the magnitude of the effect using a meta-analytical approach.MethodsSix databases were searched for randomized control trials (RCTs). The primary outcome was the sleep quality using the Pittsburgh sleep quality index (PSQI) measurement of self-reported scores, and the secondary outcomes included total sleep time and sleep efficiency measured by actigraphy. Meta-analyses were performed with the random effects model using the RevMan software. The standardized mean difference (SMD) of the PSQI scores and other measures with their 95% confidence intervals (CIs) were used for assessing the treatment effect (CRD42023370947).ResultsNine RCTs were identified and included in the study. Light therapy significantly improved the self-reported sleep quality with a reduction of the pooled PSQI score (SMD = −0.72; 95% CI: −1.24 to −0.21; p = 0.006). Regarding total sleep time (p = 0.72) and sleep efficiency (p = 0.47), no significant effects of light therapy were found.ConclusionLight therapy could improve self-reported sleep quality in cancer patients. However, due to the heterogeneity and small sample size of the included trials, the results should be interpreted cautiously. Trials with better designs and larger sample sizes are suggested to be conducted for a more definitive conclusion.Systematic review registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=370947.